2012
DOI: 10.1051/0004-6361/201117880
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of ultracompact X-ray binaries

Abstract: Context. Ultracompact X-ray binaries (UCXBs) typically consist of a white dwarf donor and a neutron star or black hole accretor. The evolution of UCXBs and very low mass ratio binaries in general is poorly understood. In particular, the dynamical behavior of an accretion disk extending to a large radius (relative to the orbit) is unclear. Aims. We investigate the evolution of UCXBs in order to learn for which mass ratios and accretor types these systems can exist, and if they do, what are their orbital and neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(125 citation statements)
references
References 85 publications
(137 reference statements)
4
120
0
1
Order By: Relevance
“…UCXBs are X-ray binaries in which the donor is an evolved star in a tight P orb 90 min orbit. Baglio et al (2016) estimated the time-averaged mass-accretion rate of RXS J1804 based on RXTE/ASM and MAXI monitoring, and concluded that this is broadly consistent with the source having a He-rich donor in a ≃40 min orbit, based on a comparison with the disk instability model (Lasota (2008); see also the evolutionary tracks of van Haaften et al (2012)). …”
Section: On the Possible Detection Of A Disk Windmentioning
confidence: 76%
“…UCXBs are X-ray binaries in which the donor is an evolved star in a tight P orb 90 min orbit. Baglio et al (2016) estimated the time-averaged mass-accretion rate of RXS J1804 based on RXTE/ASM and MAXI monitoring, and concluded that this is broadly consistent with the source having a He-rich donor in a ≃40 min orbit, based on a comparison with the disk instability model (Lasota (2008); see also the evolutionary tracks of van Haaften et al (2012)). …”
Section: On the Possible Detection Of A Disk Windmentioning
confidence: 76%
“…For each donor composition, the evolution after the stage described in Sect. 2.3.1 follows the tracks described in van Haaften et al (2012b). Initially, the white dwarf donor has not yet cooled and therefore is larger than a zerotemperature white dwarf of the same mass.…”
Section: White Dwarf Donor Systemsmentioning
confidence: 96%
“…For a 1.4 M neutron star companion, white dwarfs with a mass higher than ∼0.83 M experience dynamically unstable mass transfer, assuming a zero-temperature (completely degenerate) mass-radius relation for the donor (e.g. Yungelson et al 2002;van Haaften et al 2012b). This assumption implies that these white dwarfs have cooled considerably by the time they eventually fill their Roche lobe, although tidal heating and irradiation before the onset of mass transfer may counteract this for a short time 2 .…”
Section: White Dwarf Donor Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For two sources the average count rate is negative so the circle is not shown. The vertical dotted line at 28 min represents the orbital period above which a helium accretion disk becomes subject to the thermalviscous instability, based on the zero-temperature white dwarf donor model by van Haaften et al (2012b).…”
Section: Signal-to-noise Thresholdmentioning
confidence: 99%